Lodging in La Crosse, Wisconsin, 1880s - Brown, Richard W. (My University, 1992)
The following is a study of the phenomenon of lodging in La Crosse between 1880 and 1890. Using historical, visual and quantitative evidence, it will examine patterns of distribution, ethnic and occupational factors, and patterns of success and failure. The use of this focus will provide a new look at the social, economic, and ideological makeup of a community in the midst of transformation.
Keywords: Hotels -- Wisconsin -- La Crosse -- History -- 19th century; Boardinghouses -- Wisconsin -- La Crosse -- History -- 19th century